PROFESSIONAL DIGITAL COMPETENCY OF ENGLISH TEACHER: GENERATION DIFFERENCES - Wulan Yulian Anggini; Imam Santosa (Universitas Indraprasta PGRI, 2023)
Teacher professionalism has been instrumental in the understanding of the development of teacher competency This study, this study aims to examine the level of PDC of English teacher among different generation. This study used the method of qualitative research with the approach of descriptive interpretative analysis This study employed a descriptive interpretive analytic approach in qualitative research. The subject of this research involved of English teachers in JABODETABEK from the junior high, senior high, and vocational school levels. The result showed that each generation has a different PDC level. Teachers who are involved as baby boomers, Gen X, and millennial, since there is only one Gen Z teacher. Furthermore, teachers who are baby boomers have a high percentage of level none, knowledge, and skills because of the limited respondents. Moreover, teachers who are Gen X have more PDC points with a level of none, knowledge, and skills rather than other generations. In addition, a teacher who is Gen Z has reached competence level in all PDC points. These indicate that each generation has a different PDC level, particularly the preceding generations such as baby boomers, Gen X, and millennial